International aspects of the great depression and the crisis of 2007: similarities, differences, and lessons - National Bureau of Economic Research, Cambridge; Grossman, Richard S.; Meissner, Christopher (Cambridge, MA, 2010)
"We focus on two international aspects of the Great Depression--financial crises and international trade-- and try to discern lessons for the current economic crisis. Both downturns featured global banking crises which were generated by boom-slump macroeconomic cycles.During both crises, world trade collapsed faster than world incomes and the trade decline was highly synchronized across countries.In the Depression, income losses and rises in trade barriers explain trade collapse. Due to vertical specialization and more intense trade in durables, today trade collapse is due to uncertainty and small shocks to trade costs hitting international supply chains. So far, the global economy has avoided the global trade wars and banking collapses of the Depression perhaps due to improved policy. Even so, the global economy remains susceptible to large shocks due to financial innovation and technological change as recent events illustrate.